Associations between sleep disturbances, personality, and trait emotional intelligence. (1st March 2017) - Emert, Sarah E.; Tutek, Joshua; Lichstein, Kenneth L.
Abstract: Insomnia, difficulty falling asleep, staying asleep, or waking earlier than desired, is often associated with complaints of nonrestorative sleep, but these complaints can occur independently. Fragmented sleep and nonrestorative sleep relate to one's mood, ability to process their own or others' emotions, and can lead to changes in cognitions and behaviors. Personality traits related to increases in anxiousness may play a role in the development and maintenance of sleep disorders and associated daytime impairment of nonrestorative sleep. Relations between sleep disturbance, personality traits, and trait emotional intelligence are underrepresented and findings are mixed. This study addressed inconsistencies by identifying associations between the Big Five personality traits, trait emotional intelligence, complaints of nonrestorative sleep, and disrupted sleep associated with insomnia using a sample of university students. We predicted that neuroticism would relate to poorer sleep, and that conscientiousness and trait emotional intelligence would be associated with better sleep. Openness to experience, extraversion, and agreeableness are rarely discussed in the literature, but were expected to associate similarly to conscientiousness. Results provided support that trait characteristics are associated with insomnia severity and restorative sleep quality. Highlights: Trait characteristics are associated with insomnia symptoms and nonrestorative sleep. Higher trait emotional intelligence was associated with fewer sleep complaints. Higher neuroticism was associated with more sleep complaints. Higher conscientious was associated with fewer sleep complaints. Participants higher in openness to experience had more severe insomnia symptoms.